Impact of Structured Early Clinical Exposure on Confidence and Competence among Undergraduate Health Science Students in Islamabad: Clinical Exposure on Student Confidence - Aman, Khaliq; Hassan, Bilqis; Qamar, Zaineb; Riaz, Wajiha; Gohar, Humera; Abdullah, Sadaf (Pakistan Journal of Health Sciences, 2025)
Transitioning from classroom to clinical settings can be overwhelming for undergraduate health sciences students. Early Clinical Exposure (ECE) has been proposed to enhance confidence and competence during early training, yet its impact remains under-evaluated in local contexts. Objective: To assess the effect of structured early clinical exposure on the self-reported confidence and perceived competence of undergraduate medical, dental, and nursing students. Methods: This quasi-experimental pretest-posttest study was conducted from November 2024 to April 2025 at Rawal Institute of Health Sciences, Islamabad. A total of 71 students from 3rd, 4th, and final year were enrolled through convenience sampling. Participants completed a validated self-assessment questionnaire before and after a structured ECE session, which included classroom orientation, ward rotations, bedside interaction, and debriefing. The tool was pilot tested and showed strong internal consistency (Cronbach’s alpha = 0.86). Paired t-tests and chi-square tests were used for analysis (p < 0.05). Results: Post-intervention scores showed significant improvements across all five domains of clinical confidence, including history taking, communication, examination skills, case presentation, and anxiety management (p < 0.001). Gender was significantly associated with comfort in ward settings and understanding hospital hierarchy. No significant differences were observed across academic years. Conclusions: Structured early clinical exposure significantly enhanced students’ clinical confidence and preparedness across domains. Integrating ECE into undergraduate curricula can foster smoother transitions into clinical environments.